Akibat Hukum Pengangkatan Anak menurut Undang-Undang Nomor 23 Tahun 2002 tentang Perlindungan Anak - Adawiyah Nasution (Universitas Medan Area, 2019)
The purpose of this study is to assess the legal provisions of the children under Law No. 23 of 2002 and to explain the consequences of the child's adoption law. In addition, to know the legal protection of adopted children under the Child Protection Act is reviewed from Islamic Law Preformance law Practice in Indonesia. To examine the matter, a descriptive study was conducted with a normative juridical approach that was conducted only on the written rules. The collection of data is derived from the literature research and supported field research studies on the appointment of Court and Civil registry office. Primary data collection tools are informant with the interview guidelines whereas data analysis is done with a qualitative approach using the logical and inductive thinking logic in the field of law. In the content of this article shows that, firstly, the consequences of child adoption generally arise with the appointment of a court by not deciding the adoption of adopted children with their biological parents, which switching is the right of custody. In the case of inheritance, the appointment of children based on the determination of the Court of Justice is entitled to the inheritance of his adoptive parents based on wills. Thirdly, with the determination of the adoption of children from the courts, the consequence is the protection of adopted children can be assured of the custody of the law and the inheritance of its adoptive parents.